The effectiveness of banking risk management in granting credit: an analytical study of a sample of private Iraqi banks - Assistant teacher: Alaa Ali Saleh Al-Azirjawi*; Assistant teacher: Ghassan Ali Abdul Hassan Al-Khafaji (مجلة الدراسات الاقتصادية والادارية)
The study aims to manage banking risks (as a goal) theoretically and practically, identify the most important types of banking risks that the bank may be exposed to, and use models for each risk and the total risk to reach the risk value. The current study examines the relationship between banking risks and granting credit. The study was conducted on a sample of banks listed on the Iraq Stock Exchange, which included (13) banks, based on the financial data published in the Iraq Stock Exchange for the period (2010) to (2022). In order to achieve the objectives of the study, financial analysis of the data represented by indicators of banking risk management and bank credit was used. The study reached a set of conclusions, the most important of which are: The results of market risks showed that these banks were more cautious when it came to interest rate risks, which strengthened their banking operations, and that the continuous fluctuations in interest rates have a significant impact on interest rate risks, which may lead to gains or losses for the bank, despite the availability of some financial tools. The study recommended the need to enhance the comprehensive culture of risk management by providing instructions and training on dealing with data, predicting potential risks that the bank may be exposed to, and relying more on issuing loans to enhance profits so that banks can invest in opportunities that It allows them to change interest rates and take advantage of economic shifts. To do this, banks will need to study potential opportunities and threats and take various precautions, such as establishing and expanding risk management departments within the banks included in the study sample, hiring foreign consulting firms to help assemble the banks’ investment portfolio, and seeking to incorporate the provisions of the Basel III Committee, which provides basic guarantees to insulate banks from potential risks.